Construction Management Analysis in Shop House Building Construction Project Using Ms. Project (Case Study: Techno Park Mundu Building) - Husein Abdul Nurrasyid; Sahlan Sugiarto; Asep Rian Hidayat; Arief Firmanto (Return : Study of Management, Economic and Bussines, 2025)
This study examines the construction management of the Royal Techno Park Mundu Cirebon project using Microsoft Project software. The background of this research arises from the increasing complexity of construction projects in Indonesia, which demand effective project management to control time, cost, and resources. The research employs a mixed-methods approach, combining quantitative and qualitative methods through literature reviews, field surveys, and secondary data from relevant agencies. Analysis is carried out using scheduling techniques such as Bar chart, S-Curve, and Critical Path Method (CPM) to optimize resource allocation and accurately monitor project progress. The findings indicate that utilizing Microsoft Project enhances planning accuracy and project control, thereby minimizing the risk of delays and cost overruns. Moreover, a comprehensive needs analysis regarding materials, labour, equipment, and costs proves crucial for successful project execution. This study also emphasizes the importance of integrating information technology into planning and implementation processes, which facilitates real-time monitoring and responsive decision-making. Thus, structured construction management and periodic evaluations are key to achieving optimal and efficient construction outcomes. These findings are expected to serve as a reference for practitioners and academics in developing construction management strategies in the digital era.